Effect of self-care education on self-efficacy of patients with multiple sclerosis: a randomized clinical trial - Zahra Rooddehghan; Mohammad Saber Sholehvar; Soraya Nejati; Shima Haghani; Raoofeh Karimi (BMC Psychology)
Abstract Background Self-care education is one method used to reduce the complications of chronic diseases like Multiple sclerosis which affects self-efficacy. The present study evaluated the effect of self-care training by nurses on the self-efficacy of patients with multiple sclerosis. Methods This is a randomized clinical trial with pre-test/ post-test. The statistical population of this study included all patients with multiple sclerosis who were members of the Iranian Multiple Sclerosis Association, from whom 90 patients were selected and divided into two groups of intervention and control (n = 45 people in each group), through a table of random numbers. First, both groups completed the demographic information and Sherer's self-efficacy questionnaire. Then, a self-care empowerment program was delivered to patients in the intervention group. Eight weeks later, the self-efficacy questionnaires were completed again by both intervention and control groups. The data were analyzed using SPSS-22 statistical software. Results The mean self-efficacy score in the intervention group was (60.27 ± 8.63) and in the control group was (59.07 ± 6.84) before the intervention. After the intervention, a statistically significant difference was observed between the two groups regarding the mean self-efficacy scores (p = 0.004). The mean self-efficacy scores in the intervention and control groups were (63.73 ± 6.97) and (59.21 ± 6.23) after the intervention. Conclusions A Self-care training program can be used as one of the methods to improve self-efficacy in patients with multiple sclerosis. Trial registration The protocol of this clinical trial has been registered in the Iranian Clinical Trial Registration Center (registration code: IRCT20180914041036N1). Registered 18 January 2019- Retrospectively registered, date of first recruitment: 23 August 2017, https://www.irct.ir/ .